Prevalence of multiple myeloma and its complication in a tertiary medical college at Calicut district, India - N., Ramani P.; V., Sreeraj; Binub, Kanniyan (International Journal of Research in Medical Sciences, 2019)
Background: Multiple myeloma is a blood cancer that develops in the bone marrow, which is soft, spongy tissue found in the center of many bones where blood cells are produced. In myeloma, plasma cells, which are normal antibody-producing cells, transform into cancerous myeloma cells. The objectives of this study was the prevalence and complications of multiple myeloma. Methods: A cross sectional study was conducted in a tertiary hospital at Calicut. Semi structured questionnaire was used to study the prevalence and associated complications of multiple myeloma. History taking, physical examinations and investigations like hemoglobin estimation, peripheral smear, electrophoresis, renal function test, calcium estimation, X-ray of thoracic, lumbar spine, humerus, hip region was done. There was also an attempt to find co-morbidities hypertension, diabetes mellitus and neurological abnormalities. The variables was entered into excel and data were expressed in tables. Results: The prevalence of multiple myeloma in Calicut was found to be 77.90% of the bone marrow results were consistent with multiple myeloma. Urine Bence jone protein was positive for 22.9% of cases. Electrophoresis was done and M Band was seen positive for 78.6%. Serum blood urea value was more for 25.7% patients and 22.95% had elevated serum creatinine value. Spine compression was found among 41.4% and osteoporosis was seen in 21.4% patients. Hypertension was seen among 90% cases and Diabetes Mellitus in 4.7% of males.10 % of the patient has valvular heart disease. Conclusion: The study was able to find out the prevalence and project complications of multiple myeloma at Calicut. As there are cases in the district, present medicos who are the future doctors should be trained appropriately to diagnose and treat the disease.